COPEPTIN AS A RESEARCH MARKER IN CARDIOVASCULAR DISEASE. (June 2018) - Bosch, A.; Ott, C.; Schmid, A.; Kannenkeril, D.; Karg, M.; Ditting, T.; Veelken, R.; Uder, M.; Schmieder, R.E.
Abstract : Objective: Arginine vasopressin (ADH) is released from the neurohypophysis and regulates intravascular volume status. ADH activity is reflected by copeptin, the C-terminal peptide of pro-vasopressin. Elevated copeptin levels are associated with increased cardiovascular and all-cause mortality. The aim of this study is to compare copeptin levels in patients with different cardiovascular diseases. Design and method: In this cross-sectional analysis we measured copeptin concentrations in 69 patients with diabetes mellitus type 2 (T2DM), 30 patients with primary hypertension stage 1 or 2 (HT1–2), 34 patients with treatment resistant hypertension (TRH) (21 of them with T2DM), and 28 healthy individuals, who participated in clinical trials. In 2 study groups we analyzed changes after therapeutic interventions. Patients with T2DM received 6 weeks of treatment with 25 mg empagliflozin or placebo. Patients with TRH underwent full four quadrant renal denervation (RDN) by an experienced interventionalist. Copeptin concentrations were measured before and after treatment using Time Resolved Amplified Cryptate Emision method. Results: Patients with TRH showed higher copeptin levels than patients with HT1-2 (median 8.4 [interquartile range 3.6-14] vs. 4.2 [2.8–6.3]pmol/l, p = 0.039), patients with T2DM (4.5 [3.3–7.2]pmol/l, p = 0.020) and healthy individuals (5.7 [2.9–9.2]pmol/l, p = 0.024). There was no significant change in copeptin levels in patients with TRH before and 6 month after RDN (8.4 [3.6–14] vs 8.5 [4.5–13]pmol/l, p = 0.334), even though 24 h ambulatory blood pressure decreased from 154 ± 15/ 87 ± 12 mmHg (p = 0.001) to 146 ± 13/ 83 ± 7.9 mmHg (p = 0.034). In patients with T2DM (double blind randomized cross-over trial), no significant change in copeptin levels was observed in the placebo group compared to baseline (5.08 ± 2.83 vs 5.76 ± 4.05 pmol/l, p = 0.09), whereas treatment with empagliflozin increased copeptin levels compared to baseline (6.87 ± 3.89 pmol/l, p = 0.001). Patients receiving empagliflozin showed higher copeptin levels (p < 0.001) compared to placebo. Conclusions: Patients with TRH showed higher copeptin levels than patients with HT1-2, T2DM and healthy individuals. RDN did not lead to any change of copeptin levels in patients with TRH, but empagliflozin, as expected induced an increase in copeptin levels due to volume contraction in patients with T2DM. Copeptin emerged as a valuable research marker in cardiovascular disease.